Face-Sensitive Processes One Hundred Milliseconds after Picture Onset - Dering, Benjamin; Martin, Clara D.; Moro, Sancho; Pegna, Alan J.; Thierry, Guillaume (Frontiers in Human Neuroscience, 2011)
The human face is the most studied object category in visual neuroscience. In a quest for markers of face processing, event-related potential (ERP) studies have debated whether two peaks of activity –P1 and N170– are category-selective. Whilst most studies have used photographs of unaltered images of faces, others have used cropped faces in an attempt to reduce the influence of features surrounding the “face-object” sensu stricto. However, results from studies comparing cropped faces with unaltered objects from other categories are inconsistent with results from studies comparing whole faces and objects. Here, we recorded ERPs elicited by full-front views of faces and cars, either unaltered or cropped. We found that cropping artificially enhanced the N170 whereas it did not significantly modulate P1. In a second experiment, we compared faces and butterflies, either unaltered or cropped, matched for size and luminance across conditions, and within a narrow contrast bracket. Results of experiment 2 replicated the main findings of experiment 1. We then used face-car morphs in a third experiment to manipulate the perceived face-likeness of stimuli (100% face, 70% face and 30% car, 30% face and 70% car, or 100% car) and the N170 failed to differentiate between faces and cars. Critically, in all three experiments, P1 amplitude was modulated in a face-sensitive fashion independent of cropping or morphing. Therefore, P1 is a reliable event sensitive to face processing as early as 100 ms after picture onset.